Evaluation of the PCR-based T cell receptor-β clonality test in the diagnosis of early mycosis fungoides. (October 2021) - Barzilai, Aviv; Schachter, Orit Schachter; Debby, Assaf; Segal, Oz; Baum, Sharon; Tabibian-Keissar, Hila
Abstract : Background: T-cell receptor (TCR) clonality is important for mycosis fungoides (MF) diagnosis. Routine clonality analysis is performed using a polymerase chain reaction (PCR) TCR-γ assay; yet with this method 10–50% of T-cell lymphomas escape detection. TCR-β gene rearrangement is an additional assay. Data about its efficacy is controversial. Objective: Evaluate the role of TCR-β assay in the diagnosis of early MF. Methods: A retrospective study of 61 skin biopsies, 20 from MF patients, 30 from patients suspected to have early MF, and 11 from patients with chronic inflammatory skin disease. Results: Monoclonality was detected in 16/20 (80%) MF cases; 15 (75%) with TCR-β and 12 (60%) with TCR-γ assay. Of the 30 suspected early MF cases, 14 demonstrated monoclonality, all of which with TCR-β and 5 with TCR-γ assay. None of the chronic inflammatory condition samples showed monoclonality. Therefore, TCR-β clonality assay was more sensitive in early MF than TCR-γ (83% vs. 43%, P=0.002). Limitations: A retrospective, relatively small study. Conclusion: TCR-β demonstrated a higher sensitivity rate compared with TCR-γ in early-stage MF. The combined use of the TCR-β and TCR-γ clonality tests can significantly improve the diagnosis rate of early-stage MF.